Efektivitas Minyak Serai Sebagai Bioinsektisida Nyamuk - Sari, Vebrita; Gafur, Abdul; Sari, Desi Ratna (Journal of Engineering Science and Technology Management (JES-TM), 2023)
The Universitas Pahlawan Tuanku Tambusai (UPTT) campus allows it to become a preferred habitat for mosquitoes while laying their eggs. Aedes sp. is a vector for the spread of Dengue Hemorrhagic Fever (DHF). One way to control dengue fever is to use insecticides. The use of insecticides that are excessive and repeated can have a negative impact, for that we take advantage of the potential of nature as a bioinsecticide. One of them is the lemongrass plant which can be used as a mosquito repellent because it contains substances such as geraniol, methyl heptenone, terpenes, terpenes, organic acids and especially citronella as a mosquito spray. This research is a quantitative research with a pure experimental design. Researchers made observations in the field to collect mosquito larvae, which were then reared in the laboratory. The results of rearing mosquitoes were then treated and analyzed using WHO mosquito mortality standard criteria. Lemongrass plants can be used as bioinsecticides or insect organic insecticides, for example the Aedes sp. Lemongrass plant extract (Cymbopogon citratus) is effective in killing Aedes sp. mosquito larvae. along with increasing concentration in each treatment. The most potent or effective concentration in killing Aedes sp. is a concentration of 20%.